Faktor yang Berhubungan dengan Tingkat Stress Mahasiswa Jawa Timur saat Pandemi COVID-19 - Mustikawati, Erlian Indah; Efendi, Kaoline Eki Maharani Putri (Preventif : Jurnal Kesehatan Masyarakat, 2023)
The implementation of educational system policy during the COVID-19 pandemic is applying distance learning methods for college students that could be done from home. The differences learning methods require students to deal with the transition process that can lead to stress. The purpose of this study was to analyze factors related to the stress level of East Java college students during the COVID-19 pandemic. This type of research is a quantitative online research with a cross-sectional research design by distributing questionnaires via google form. The total sample obtained in this study amounted 123 East Java college students. Data were analyzed using chi-square test in IBM SPSS Statistics application. The results showed that the majority of respondents experienced mild stress (43.1%) during the COVID-19 pandemic. The results also show that there is a significant relationship between gender (p value = 0.033) and the level of loneliness (p-value = 0.000) with the stress level of East Java college students during the COVID-19 pandemic. The prevention action to overcome college students' stress problems are periodic checks on college students' mental health conditions and handling college students’ stress during the COVID-19 pandemic.